2007
DOI: 10.1051/0004-6361:20078931
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of a reverse shock in magnetized gamma-ray burst ejecta

Abstract: The role of magnetic fields in gamma-ray burst (GRB) flows remains controversial. The study of the early afterglow phases and, in particular, of the reverse shock dynamics and associated emission offers a promising probe of the magnetization of the ejecta. In this paper, we derive the conditions for the existence of a reverse shock in arbitrarily magnetized ejecta that decelerate and interact with the circumburst medium. Both constant and wind-like density profiles are considered. We show, in contrast to previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 61 publications
8
83
1
Order By: Relevance
“…The FS is stronger (due to a higher jump in pressure) and slower (more deceleration relative to the frame of the contact discontinuity), while the RS is weaker but faster. These features are expected from analytical work, 10,14 and agree with 1D relativistic MHD simulations. 17,18 For σ = 10.0 (dashed) and σ = 20.0 (dash-dotted), a prominent left-going rarefaction wave ( ← R) is observed, instead of a left-going shock.…”
Section: Flow-medium Interactionsupporting
confidence: 83%
See 2 more Smart Citations
“…The FS is stronger (due to a higher jump in pressure) and slower (more deceleration relative to the frame of the contact discontinuity), while the RS is weaker but faster. These features are expected from analytical work, 10,14 and agree with 1D relativistic MHD simulations. 17,18 For σ = 10.0 (dashed) and σ = 20.0 (dash-dotted), a prominent left-going rarefaction wave ( ← R) is observed, instead of a left-going shock.…”
Section: Flow-medium Interactionsupporting
confidence: 83%
“…Exact solutions indicate that the condition for the existence of a reverse shock is σ < σ c . 10,14 The paucity of bright optical flashes in GRBs 22 may, among other interpretions, be attributed to highly magnetized flows. If strongly magnetized jet (Poynting flux jet) is formed and leaves from the dense stellar matter like a collapsar model and goes to rarefied wind media, it is possible to form the bow-shock with the rarefaction wave on the jet head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of analytic and numerical papers on magnetization. The existence of a reverse shock (RS) in magnetized ejecta was suggested (e.g., Fan et al 2004;Zhang & Kobayashi 2005;Giannios et al 2008;Mimica et al 2009;Lyutikov 2011) and the dynamics of arbitrarily magnetized ejecta-medium interaction were studied (e.g., Zhang & Kobayashi 2005;Mimica et al 2009;Mizuno et al 2009;Lyutikov 2011). It was found that the A&A 592, A92 (2016) magnetization influences the RS emission (e.g., Mimica et al 2010;Harrison & Kobayashi 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The RS, arising from the interaction of the wind with the merger ejecta and external medium, depends on the magnetization of the magnetar wind (Fan et al 2004;Zhang & Kobayashi 2005;Mimica et al 2009Mimica et al , 2010Mao et al 2010). The strong magnetic fields would suppress the RS in the magnetized wind (Fan et al 2004;Zhang & Kobayashi 2005;Giannios et al 2008;Mimica et al 2009Mimica et al , 2010.…”
Section: Introductionmentioning
confidence: 99%